Correlation of Clinical and Inflammatory Parameters in Chronic Obstructive Pulmonary Disease - Angjela, Debreshlioska; Ismaili, Irfan; Angelovska, Irina; Vuinov, Venco; Karakostova, Marija (SHMSHM - AAMD, 2023)
Aim: The aim of this study was to determine the values of systemic inflammatory parameters in patients with COPD and to determine their correlation with selected clinical parameters. Material and methods. We conducted a cross-sectional analytical study at PHI University Clinic for Pulmonology and Allergy, on 59 patients diagnosed with COPD. All patients underwent anamnesis with review of medical records for demographic and clinical data, history of allergies, cigarette smoking, and history of exacerbations. Patients completed a COPD assessment questionnaire (CAT) and a modified dyspnea scale (mMRC) and the BODE (Body mass index, Obstruction, Dyspnea, Exercise capacity) index was calculated. Spirometry and lung X-ray were performed. Peripheral blood was taken for analysis of inflammatory parameters. Results: A total of 59 patients were included, of which 14 (23.72%) were women and 45 (76.27%) were men. The mean age was 65.23 years. Statistical analysis showed a significant positive correlation between CRP and GOLD, CAT, mMRC and the existence of chronic bronchitis, as well as a significant linear moderate negative correlation between CRP and CAT. A significant linear positive correlation between Le and GOLD, CAT, mMRC and BODE, a significant linear positive correlation between Ne and GOLD, mMRC and BODE, as well as a significant linear moderate negative correlation between Ne and FEV1 were also determined. Of the cytokines Il-4 showed a significant linear moderate positive correlation with chronic bronchitis, and Il-18 a significant linear strong positive correlation with the presence of emphysema. Conclusion: The existence of a correlation between selected inflammatory and clinical parameters provides additional data that may help elucidate pathogenetic mechanisms and determine potential therapeutic targets that would personalize the approach to the patient with COPD.
Keywords: COPD; inflammatory parameters; clinical parameters